In vitro medium-term conservation of Bacopa monnieri (L.) Pennell-The Memory Plus plant-under slow-growth conditions - Satheesh, G.=700 1 Geetha, S.P.; Sudhakar Raja, S.P.; Balachandran, I.
(Es, En, Pt)
ilus., 27 ref.
Keywords: CULTIVO IN VITRO; CONSERVACION DEL GERMOPLASMA; RECURSOS GENETICOS; PLANTAS MEDICINALES; ITALIA; BACOPA MONNIERI; NOTICIARIO DE RECURSOS FITOGENETICOS